Integrating traditional ritual dance and minority culture of Western Hunan into dance instruction: Utilizing information technology to preserve China's intangible heritage. - Ma, Qiang (Digital Scholarship in the Humanities, 2023)
The goals of this study were to design an online platform devoted to preserving and studying China's intangible cultural heritage (ICH) within the limits of ritual and minority dances of western Hunan, obtain experimental data on the usefulness of the developed platform in the preservation and study of Chinese ritual and folk dances, assess dance instructors' participation in ICH preservation through information technology (IT), and identify IT means able to preserve China's ICH within the framework of higher education dance instruction in China. For these aims to be achieved, the layout and structure of the platform with audio/video/photo materials, animations, and 3D models were developed, and a number of educators teaching various dance disciplines at universities of China were surveyed. Overall, the study sample comprised 114 people. The platform's database was compiled by Art History postgraduates from the National Center for the Performing Arts, while its backbone was created by Beijing IT specialists. According to the carried-out assessment, photo/video materials were identified as the most popular IT means capable of preserving China's ICH as a part of dance instruction in higher education (68.4%). 3D technology was preferred by 19.3% of respondents, textual documents—by 9.6%, and virtual reality technology—by 2.7%. The practical significance of the collected data lies in the possibility of their usage in the process of creating university dance instruction curricula, modernizing instruction materials, developing online webinars, and improving the process of teaching traditional Chinese and world culture.